Intracerebral haemorrhage in a population-based stroke registry (LuSSt): incidence, aetiology, functional outcome and mortality - Palm, Frederick; Henschke, Nicholas; Wolf, J.; Zimmer, K.; Safer, Anton; Schröder, R. J.; Inselmann, G.; Brenke, C.; Becher, Heiko; Grau, Armin J. (Journal of neurology, 2013)
Data on incidence of intracerebral haemorrhage (ICH) vary widely. Population-based data on predictors of ICH survival and functional outcome are rare. The Ludwigshafen Stroke Study is a prospective, population-based stroke registry which started in January 2006. All residents of the city of Ludwigshafen, Germany, who suffer from acute stroke or transient ischaemic attack are registered. Patients with first-ever primary intracerebral haemorrhage (FE-pICH) between 2006 and 2010 were included in the present analysis. Between January 1st, 2006 and December 31st, 2010, 152 patients suffered a FE-pICH. Crude and age-adjusted incidence rates per 100,000 for FE-pICH were 18.7 (95 % CI 15.9-21.9) and 11.9 (95 % CI 10.2-14.0), respectively, and remained stable over time. Case-fatality rates for FE-pICH were 27.0, 34.9 and 44.1 % at days 28, 90 and 365, respectively. In 21 patients, an (21.3 %) early do-not resuscitate-order was documented. Excluding these patients from multivariate analyses, National Institute of Health Stroke Scale (NIHSS) (OR 1.22, 95 % CI 1.08-1.36), hypercholesterolemia (OR 0.16, 95 % CI 0.05-0.55) and modified Rankin Scale (mRS) prior to stroke (OR 1.56, 95 % CI 1.06-2.3) were independently associated with risk of 1-year mortality, whereas NIHSS (OR 1.41, 95 % CI 1.20-1.66) and leukocyte count on admission (OR 1.48, 95 % CI 1.16-1.89) were independently associated with good or moderate functional outcome (mRS ≤ 3) after 1 year. Incidence of FE-ICH is in the lower range of those reported from other registries and remained stable over the observation period. Higher treatment rates for hypertension might partly account for this. Stroke severity as indicated by NIHSS was independently associated with mortality and functional outcome after 1 year. We found no association between aetiology and outcome in ICH patients.